Answer:
Step-by-step explanation:
Let the quadratic equation of the function by the points in the given equation is,
f(x) = ax² + bx + c
If the points lying on the graph are (-3, -10), (-4, -8) and (0, 8),
For (0, 8),
f(0) = a(0)² + b(0) + c
8 = c
For a point (-3, -10),
f(-3) = a(-3)² + b(-3) + 8
-10 = 9a - 3b + 8
9a - 3b = -18
3a - b = -6 --------(1)
For (-4, -8),
f(-4) = a(-4)² + b(-4) + 8
-8 = 16a - 4b + 8
-16 = 16a - 4b
4a - b = -4 ------(2)
Subtract equation (1) from equation (2)
(4a - b) - (3a - b) = -4 + 6
a = 2
From equation (1),
6 - b = -6
b = 12
Function will be,
f(x) = 2x² + 12x + 8
= 2(x² + 6x) + 8
= 2(x² + 6x + 9 - 9) + 8
= 2(x² + 6x + 9) - 18 + 8
= 2(x + 3)² - 10
By comparing this function with the vertex form of the function,
y = a(x - h)² + k
where (h, k) is the vertex.
Vertex of the function 'f' will be (-3, -10)
And axis of symmetry will be,
x = -3
From the given graph, axis of the symmetry of the function 'g' is; x = -3
Therefore, both the functions will have the same axis of symmetry.
y-intercept of the function 'f' → y = 8 Or (0, 8)
y-intercept of the function 'g' → y = -2 Or (0, -2)
Therefore, y-intercept of 'f' is greater than 'g'
Average rate of change of function 'f' =
in the interval [a, b]
= ![\frac{f(-3)-f(-6)}{-3+6}](https://tex.z-dn.net/?f=%5Cfrac%7Bf%28-3%29-f%28-6%29%7D%7B-3%2B6%7D)
= ![\frac{-10-8}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B-10-8%7D%7B3%7D)
= -6
Average rate of change of function 'g' = ![\frac{g(b)-g(a)}{b-a}](https://tex.z-dn.net/?f=%5Cfrac%7Bg%28b%29-g%28a%29%7D%7Bb-a%7D)
=
= ![\frac{7+2}{-3+6}](https://tex.z-dn.net/?f=%5Cfrac%7B7%2B2%7D%7B-3%2B6%7D)
= 3
Therefore, Average rate of change of function 'f' is less than 'g'.